Effectiveness of Internet-Based Emotion-Focused Cognitive Behavioral Therapy (iECBT) with and without husband’s participation in improvement of psychological distress in pregnant women with anxiety disorders: a randomized controlled trial - Mojgan Shariatpanahi; Mahbobeh Faramarzi; Shahnaz Barat; Azadeh Farghadani; Hoda Shirafkan (BMC Psychology)
Abstract Background Anxiety disorders are common psychological pregnancy problems that can lead to adverse pregnancy outcomes. The study aimed to compare the improvement of psychological distress between Internet-Based Emotion-Focused Cognitive Behavioral Therapy (iECBT) with and without husbands’ participation in pregnant women with anxiety disorders. Method In a randomized controlled trial, 84 pregnant women diagnosed with anxiety disorders were randomly assigned to two groups: iECBT alone (n = 42) and iECBT with their husband’s participation (n = 42). In a group of iECBT alone, women received eight sessions of iECBT (with a duration of 50 min) once a week. In the iECBT group with the husband’s participation, women received psychotherapy as same as iECBT alone, and their husbands received eight sessions (with a duration of 20 min) once a week. The outcomes were the Spielberger State-Trait Anxiety Inventory (STAI), the Brief Symptom Inventory 18, the pregnancy-specific stress, and Garnefski’s cognitive emotion regulation in the four-time series. Results The mean age of participants was about 30 years. Both iECBTs, with and without the husband’s participation, were effective in improving state anxiety, psychological distress, pregnancy-specific stress, and emotion regulation in pregnant women. iECBTs with and without the husband’s participation were not superior to each other regarding improving the outcomes. Conclusion As iECBT with the husband’s participation was not superior to iECBT alone, further studies should evaluate proper strategies to increase men’s effective role in the treatment of their pregnant partners with psychological disorders. Trial registration IRCT20110228005931N10.